Peningkatan Motorik Halus Melalui Permainan Montessori Pada Anak Usia Dini Di PAUD Terpadu Putri Nahrisyah - Alda Zahara Islamyati; Rahimah Ulfah Harahap (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Fine motor skills involve the muscles in specific body parts. One activity that can improve fine motor skills in early childhood is Montessori play, which involves developing fine motor skills in the form of hand-eye coordination, hand and finger muscle strength, and activities such as playing with plasticine and geometric puzzles. This study aims to improve fine motor skills in early childhood through play activities at the Putri Nahrisyah Integrated Preschool. The fine motor skills studied included finger skills and eye coordination for activities. This study used classroom action research. Data analysis used qualitative data. The subjects were 3-4-year-old children at the Putri Nahrisyah Integrated Preschool. The results indicate that children's fine motor skills improved after being exposed to Montessori play activities.